ASSOCIATION OF DRY EXTRACTS OF VICIA FABA, UNCARIA RHYNCOPHYLLA AND LIQUORICE ROOT TOGETHER WITH COENZYME Q10 FOR USE AS COADJUVANT, FOR IMPROVING THE QUALITY OF LIFE IN SUBJECTS SUFFERING FROM MOVEMENT DISORDERS - BONOMO FRANCESCO; DEL BONO MARIA CRISTINA (2020)
Association comprising: dry extract of: a) Vicia faba, b) Uncaria rhyncophylla and c) liquorice root, coenzyme QIO, and preferably at least one vitamin chosen from vitamin C and E for use as coadjuvant for improving the quality of life (QOL) in subjects with movement disorders and in particular in subjects suffering from Parkinson's disease. This association is preferably in an oral formulation, more preferably in the form of a food supplement. 一种组合，其包括：-以下物质的干提取物：a)蚕豆、b)钩藤和c)甘草根，-辅酶Q10，以及优选至少一种选自维生素C和E的维生素，该组合用作用于改善患有运动障碍的患者、特别是患有帕金森氏病的患者的生活质量(QOL)的辅佐剂。该组合优选为口服制剂，更优选为食品补充剂的形式。